KINERJA USAHATANI KOPI DI HULU DAS SEKAMPUNG, TANGGAMUS, LAMPUNG - Fitriani, Fitriani; Arifin, Bustanul; Zakaria, Wan Abbas; Ismono, R. Hanung (Politeknik Negeri Lampung., 2018)
Most of the coffee production areas in Lampung are in the vicinity of production forests andprotected forests, also a catchment area for watersheds in Lampung, namely Sekampung andWay Seputih watersheds. Continuity of sustainable coffee production lines is an importantdemand that needs to be done. The application of coffee production systems with shade(agroforestry) in the catchment area is very important in ensuring environmentalsustainability. This study aims to analyze the income performance of agroforestry coffeebased on the land status in Hulu Das Sekampung. The research uses survey methods. Fielddata exploration conducted in April-November 2016 is located in Datar Lebuay and SinarJawa Villages. Air Naningan, Tanggamus, Lampung. The descriptive statistical analysismethod is used to explain the performance of agroforestry coffee production at the researchlocation. Based on the results and discussion it was concluded that farmers with landownership status had the highest level of coffee farming income compared to the land statusof HKm and non-HKm. Agroforestry coffee farmers obtain sources of income from coffeeproduction, MPTS production, and other crop production (multiple cropping). The averagecontribution of coffee farming income is 22% of the total farm income. Coffee contributes22% to the total income of farmer households. Farmer's household income with the status ofland ownership is the highest compared to the land status of HKm and Non-HKm. Thediversity of income sources of upstream farmers in the watershed. The villages that comefrom various vegetation plants are important in maintaining land cover as a catchment area.The practice of agroforestry coffee is an adaptation of sustainable production in the upperwatershed Sekampung. The pattern of agroforestry coffee production in the area aroundprotected and watershed forests needs to be continuously developed.